Health Care Experiences During Pregnancy and Parenting with an Opioid Use Disorder. Issue 2 (March 2022) - Kim, Jane; Busse, Morgan; Kantrowitz-Gordon, Ira; Altman, Molly R.
Abstract: Purpose: The purpose of this study was to describe the experience of individuals with opioid use disorder (OUD) during the perinatal period. Study Design and Methods: We convened focus groups of patients with OUD who had been pregnant and were parenting. Participants who were 18 and older, English-speaking, self-identified as pregnant or parenting, and actively using opioids or in recovery from OUD were recruited using snowball and convenience sampling in resident treatment facilities and outpatient settings. Data were recorded, transcribed, and analyzed for themes. Results: Twenty-four participants were recruited, 10 of whom were actively receiving residential recovery services. Most participants had been pregnant from 4 weeks to 2 years prior to our focus group session; none reported being currently pregnant. Nineteen participants had custody of some, or all, of their children. They identified four key themes related to their care: (1) disrespectful care, (2) fear of accessing services, (3) inconsistencies in care received, and (4) limited health and social services . Clinical Implications: Participants reported overall negative interactions across different health care settings and lack of social resources to promote ongoing recovery and successful parenting. Nurses should be aware of the lasting impressions they have on their patients. Recognition of their own biases, person-first language, and partnership building skills with patients can help attenuate OUD stigma, promote positive nurse–patient relationships, and support new parents in recovery and infant bonding. Abstract : Encounters with health care professionals and the health care system can be stressful for pregnant women and parenting women with an opioid use disorder. In this study, patients who had experienced pregnancy and postpartum while they had an opioid use disorder share their interactions with nurses and other health care professionals and their fears of the system. Based on these reports, the authors offer suggestions for enhancing nursing care for this vulnerable population.